Children's games in the new media age : childlore, media and the playground - Burn, Andrew (Andrew Nicholas); Richards, Christopher Owen (Ashgate studies in childhood, 1700 to the present., 2014)
Conceived to explore the relationship between children's vernacular play cultures and their media-based play, this collection challenges two popular misconceptions: that children's play is dying out and that it is threatened by contemporary media such as television and computer games. The result is a wide-ranging and lively investigation of gender, power and social change in contemporary children's play cultures.